QĪMATU ḤUBBIL WAṬAN FĪ SYI’RI “LIBYA JINĀḤU AL-‘URŪBBAH” LI ‘ALI ṢIDQĪ ‘ABDUL QĀDIR - Alam An Shori; Laily Fitriani; Nur Hasaniyah (Journal of Arabic Literature (JaLi), 2024)
Research on Arabic literature in Libya, especially on literature in the nationalist genre, is important to study to examine the correlation between the values of nationalism or what is commonly referred to as Pan Arabism, which Muammar Gaddafi championed, and the Libyan Arabic poetry that developed at that time. Researchers are interested in analyzing the value of love for one's country in the poem "LIBYA JINĀḤU AL-'URŪBBAH" by Ali Sidqi Abdul Qadir. In analyzing the research object, the researcher used a qualitative approach with data collection techniques in the form of reading techniques and note-taking techniques. The researcher then analyzed the data that had been recorded using Norman Fairclough's critical discourse analysis. The findings in this research are that there is a fairly strong value of love for one's homeland from the author of poetry as well as a call to love the country which is none other than Libya as the homeland of the Libyan people. The conclusion of this research is that the values and propaganda of love for the country were found in the poem after the poem was analyzed in terms of text, discourse practice, and sociocultural practice.